2011
DOI: 10.3390/ijerph8083063
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Dialkylphosphate Metabolites of Organophosphorus Pesticides: National Health and Nutrition Examination Survey 1999–2004

Abstract: Organophosphorus (OP) insecticides were among the first pesticides that EPA reevaluated as part of the Food Quality Protection Act of 1996. Our goal was to assess exposure to OP insecticides in the U.S. general population over a six-year period. We analyzed 7,456 urine samples collected as part of three two-year cycles of the National Health and Nutrition Examination Survey (NHANES) from 1999–2004. We measured six dialkylphosphate metabolites of OP pesticides to assess OP pesticide exposure. In NHANES 2003–200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 31 publications
4
48
2
Order By: Relevance
“…The presence of DAP metabolites in the Greek population has also been reported in previous biomonitoring studies in agricultural workers, in pregnant women and the general population 18–20. Comparing the levels found in this study with levels recorded in the US population in the National Health and Nutrition Examination Survey,9 we observed significant higher levels in all metabolites. In the German population,10 DMP levels were of an order of magnitude greater, while levels for the diethyl metabolites were similar.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The presence of DAP metabolites in the Greek population has also been reported in previous biomonitoring studies in agricultural workers, in pregnant women and the general population 18–20. Comparing the levels found in this study with levels recorded in the US population in the National Health and Nutrition Examination Survey,9 we observed significant higher levels in all metabolites. In the German population,10 DMP levels were of an order of magnitude greater, while levels for the diethyl metabolites were similar.…”
Section: Discussionsupporting
confidence: 66%
“…Urinary analysis of DAPs is the most frequently used technique, while other matrices, such as amniotic fluid, meconium, hair and blood have been less studied 8. Urinary levels of DAP have been detected in general population in the USA,9 Germany10 and in several other countries,11–13 indicating that exposure to OP from dietary intake and residential uses is present in non-occupationally exposed individuals. Studies had also shown elevated levels of urinary DAPs in farm workers and pesticide applicators 14.…”
Section: Introductionmentioning
confidence: 99%
“…The sum of concentrations of the dimethyl metabolites is clearly larger than the sum of diethyl metabolites (Fig. SI-1), which is in agreement with the higher number of currently-used pesticides that degrade into dimethyl metabolites, including malathion, dimethoate, phosmet or azinphos methyl (McKelvey et al, 2013;Barr et al, 2011). Nevertheless, the high rate of detection of DEP can be related with the widespread use of the insecticide chlorpyrifos (Roca et al, 2014), although DEP is common to all diethyl-substituted OP insecticides.…”
Section: Organophosphate Pesticides In Urinesupporting
confidence: 71%
“…Low concentrations of OPs are detected on fruits and vegetables, and OP metabolites are routinely detected in urine samples from adults and children living in the United States (5). During the early 1980s through the late 1990s, OPs were used extensively in homes and in agriculture, and during this same period of time the incidence of asthma increased, particularly in children (6).…”
Section: Clinical Relevancementioning
confidence: 99%